The Potential Relationship Between Environmental Endocrine Disruptor Exposure and the Development of Endometriosis and Adenomyosis - Stephens, Victoria R.; Rumph, Jelonia T.; Ameli, Sharareh; Bruner-Tran, Kaylon L.; Osteen, Kevin G. (Frontiers in Physiology, 2022)
Women with endometriosis, the growth of endometrial glands and stroma outside the uterus, commonly also exhibit adenomyosis, the growth of endometrial tissues within the uterine muscle. Each disease is associated with functional alterations in the eutopic endometrium frequently leading to pain, reduced fertility, and an increased risk of adverse pregnancy outcomes. Although the precise etiology of either disease is poorly understood, evidence suggests that the presence of endometriosis may be a contributing factor to the subsequent development of adenomyosis as a consequence of an altered, systemic inflammatory response. Herein, we will discuss the potential role of exposure to environmental toxicants with endocrine disrupting capabilities in the pathogenesis of both endometriosis and adenomyosis. Numerous epidemiology and experimental studies support a role for environmental endocrine disrupting chemicals (EDCs) in the development of endometriosis; however, only a few studies have examined the potential relationship between toxicant exposures and the risk of adenomyosis. Nevertheless, since women with endometriosis are also frequently found to have adenomyosis, discussion of EDC exposure and development of each of these diseases is relevant. We will discuss the potential mechanisms by which EDCs may act to promote the co-development of endometriosis and adenomyosis. Understanding the disease-promoting mechanisms of environmental toxicants related to endometriosis and adenomyosis is paramount to designing more effective treatment(s) and preventative strategies.